Sustainable institutional investors, corporate sustainability performance, and corporate tax avoidance: Empirical evidence for the European capital market - Patrick Velte (Corporate Social Responsibility and Environmental Management, 2023)
This study addresses the influence of sustainable institutional investors (SII), based on the signatory status of the UN Principles for Responsible Investment (PRI), on corporate tax avoidance. Moreover, the moderating influence of corporate sustainability performance (CSP) is analyzed. The analyses concentrate on a European sample consisting of 1689 firm-year observations between 2014 and 2020 (EUROSTOXX 600) embedded in a stakeholder agency theoretical framework. Correlation, regression, and robustness analyses are conducted. The results are in line with prior studies on equity ownership and tax avoidance and indicate that SII have a negative impact on tax avoidance and that CSP strengthens this negative effect. These results are robust to a battery of sensitivity analyses. SII represent a major monitoring mechanism in promoting responsible tax behavior, which is in line with other stakeholders' interests. Tax avoidance should be integrated into overall sustainability management to realize an increased firm reputation. As the European Commission initiated several regulations on sustainable finance, sustainability reporting, and tax disclosure, the empirical results stress the interdependencies between ownership structure, CSP, and tax avoidance. The study makes a major contribution to prior analyses, as this study is the first to assess the link between SII and tax avoidance and the moderating impact of CSP to urge top management to increase sustainability efforts.
Keywords: 650; corporate sustainability performance; stakeholder agency theory; sustainable corporate governance; sustainable institutional investors; tax avoidance